Les avatars de la mère. La réécriture de soi dans le monde de Michel Tremblay - Kapołka, Karolina (Romanica Silesiana)
Although the works of Michel Tremblay are replete with references to other authors, it is the phenomenon of autotextuality that becomes the focal point of the analysis in this article. The author of “Chroniques du Plateau Mont-Royal” and numerous plays and novels binds them all together by resorting to the recurrence of his figures. Thus, the figure of Mother, a figure grafted onto the network of Michel Tremblay’s works, undergoes a metamorphosis from boisterous and authoritarian Nana Tremblay (in the autobiographical prose and drama) to a symbol of ideal motherhood embodied by The Great Mother of Tremblay’s universe. She gives the beginning to both new life and new writing and hence she becomes her writer-son’s inspiration and creative muse. Key words: Michel Tremblay; autotextuality; metamorphoses; mother; writing